2016
DOI: 10.1148/radiol.2016151229
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness Value and Serum Biomarkers in Liver Fibrosis Staging: Study in Large Surgical Specimens in Patients with Chronic Hepatitis B

Abstract: Purpose To investigate the capabilities of stiffness value and serum biomarkers in the staging of liver fibrosis in patients with chronic hepatitis B (CHB), with pathologic findings in large surgical specimens serving as the reference standard. Materials and Methods This study was approved by the institutional review board, and informed consent was obtained from all patients. Liver stiffness (determined by means of ultrasonography-based elastography point quantification), aspartate aminotransferase-platelet ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
5
29
0
1
Order By: Relevance
“…13,25 In our study, we found the same moderate sensitivity and accuracy of APRI and FIB-4 in diagnosing advanced liver fibrosis and cirrhosis as shown in a prior meta-analysis. Lu et al, 28 in a large cohort of chronic HBV patients, reported significantly higher AUCs for liver stiffness (measured by point shear wave ultrasound elastography) than for APRI and FIB-4 in identification of all stages of liver fibrosis. Lu et al, 28 in a large cohort of chronic HBV patients, reported significantly higher AUCs for liver stiffness (measured by point shear wave ultrasound elastography) than for APRI and FIB-4 in identification of all stages of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,25 In our study, we found the same moderate sensitivity and accuracy of APRI and FIB-4 in diagnosing advanced liver fibrosis and cirrhosis as shown in a prior meta-analysis. Lu et al, 28 in a large cohort of chronic HBV patients, reported significantly higher AUCs for liver stiffness (measured by point shear wave ultrasound elastography) than for APRI and FIB-4 in identification of all stages of liver fibrosis. Lu et al, 28 in a large cohort of chronic HBV patients, reported significantly higher AUCs for liver stiffness (measured by point shear wave ultrasound elastography) than for APRI and FIB-4 in identification of all stages of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…26 Also, as reported previously by Huwart et al, 27 we showed that MRE was superior to blood tests (APRI and FIB-4) in our study. Lu et al, 28 in a large cohort of chronic HBV patients, reported significantly higher AUCs for liver stiffness (measured by point shear wave ultrasound elastography) than for APRI and FIB-4 in identification of all stages of liver fibrosis. Our results are in concordance with extensive literature showing that serum biomarkers are less reliable for discriminating between intermediate fibrosis stages and can be influenced by the presence of extrahepatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Great strides in imaging technique have been made for staging hepatic fibrosis. Noninvasive measurement of liver stiffness with elastometry, such as transient elastography, shear‐wave elastography, and MR elastography, has shown high accuracy for staging hepatic fibrosis, but the dedicated device is costly and its availability is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported low positive predictive value of APRI and FIB‐4 index for significant fibrosis in CHB patients with persistently normal and mildly elevated ALT, indicating that liver biopsy was still needed for those patients who have FIB‐4 >1.45 or APRI >0.5 . In the latest study of Lu et al, APRI and FIB‐4 showed relatively poor diagnostic accuracy in discriminating fibrosis of stage 4 (AUCs, 0.68 and 0.67, respectively) …”
Section: Discussionmentioning
confidence: 99%
“…According the previous studies, the 5-year survival could reach up to 78.3% for the Milan criteria, 72.4% for the UCSF, 71.2% for the up-to-seven and 72.3% for the Hangzhou criteria [4][5][6]. Recently, large sample size studies from eastern and western liver transplantation centers had reported the superiority of transplantation over resection for HCC beyond the Milan criteria without major vascular invasion [3,7]. Moreover, study from Bruix, et al and Volk et al suggested that transplantation for HCC without dropping to 50% of 5-year overall survival was acceptable [8,9].…”
Section: Introductionmentioning
confidence: 99%